PELATIHAN PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM PENTOL’E CAK MOHA - Dian Fahriani; Alfira Anggraini; Ambar Wadhah; Siti Syarifah; Ferdiana Prameswari (Abdi Jurnal Publikasi, 2023)
UMKM is an abbreviation of micro, small and medium enterprises. MSMEs are productive economic enterprises run by individuals or small business entities. As a business actor who produces a product, you should know the cost of making the product using the cost of production formula. Before discussing further about the formula for determining the cost of production, it is better to know what is meant by the cost of production itself. Basically, the cost of production is a list of costs that need to be issued during the production process within a certain period. In calculating industrial production costs, there are several elements that must be considered, namely direct material costs, labor costs, and factory overhead costs. The process of calculating the cost of production is useful for increasing knowledge for owners of small companies engaged in production. The research uses qualitative methods for data collection by interviewing the owner of the Pentol'e Cak Moha UMKM. The purpose of this PkM program is to find out the calculation of the cost of production at Pentol'e Cak Moha UMKM and this PkM program is expected to be input and information for Pentol'e Cak Moha UMKM in terms of calculating product cost of goods, which is in accordance with the accounting system.